In Silico Screening of Some Anti-Cancer Drugs Against the Main Protease of COVID-19 Using Molecular Docking - Ouni, Leila; Ramazani, Ali (Letters in Organic Chemistry, 2023)
The SARS-CoV-2 pandemic has led to major worldwide health concerns. Design and detection of effective drugs and adjuvant therapies to treat COVID-19 disease in the shortest possible time have become one of the most critical global challenges. In this study, we investigated the effect of some anticancer drugs against the COVID-19 main protease (Mpro/3CLpro) to detect an effective treatment, using a molecular docking approach as a fast and cost-effective method. Accordingly, 44 anticancer drugs were selected as a target for the virtual screening. The molecular docking study was carried out using AutoDock Tools (ADT), AutoDock Vina, Discovery Studio, and Open Babel software. Tucatinib, selinexor, irinotecan, olaparib, dacomitinib, lapatinib, ibrutinib, and pazopanib were ranked top as COVID-19 inhibitors with the respective binding energy of -10.1, -9.4, -9.2, -8.9, -8.7, -8.7, -8.6, and -8.5 kcal/mol. Among the drugs tested, tucatinib displayed the highest binding affinity and strong interactions with the active site of COVID-19 3CLpro (-10.1 kcal/mol). Pharmacokinetics properties and drug-likeness of the top 8 selected anticancer drugs were evaluated. The results showed that these drugs could be utilized as potential inhibitors against the main protease of COVID-19, which can help control the spread of this disease. However, in vitro, in vivo studies, and clinical trials will help evaluate the efficacy of these drugs against COVID-19.
Keywords: COVID-19 main protease